Moderate levels of physical fitness maintain telomere length in non-senescent T CD8+ cells of aged men - Marta Ferreira Bastos; Manuella de Sousa Toledo Matias; Angélica Castilho Alonso; Léia Cristina Rodrigues Silva; Adriana Ladeira de Araújo; Paulo Roberto Silva; Gil Benard; Danilo Sales Bocalini; Julien Steven Baker; Luiz Eugênio Garcez Leme (Clinics)
OBJECTIVES: Immunosenescence is an age-associated change characterized by a decreased immune response. Although physical activity has been described as fundamental for maintaining the quality of life, few studies have evaluated the effects of different levels of exercise on telomere length in aged populations. The present study aimed to analyze the effects of different levels of physical activity, classified by the Maximal oxygen consumption (VO2 max) values, on the telomere length of memory Cluster of differentiation (CD) CD4+(CD45ROneg and CD45RO+), effector CD8+CD28neg, and CD8+CD28+ T cells in aged individuals. METHODS: Fifty-three healthy elderly men (aged 65-85 years) were included in this study. Their fitness level was classified according to the American College of Sports Medicine (ACSM) for VO2 max (mL/kg/min). Blood samples were obtained from all participants to analyze the percentage of CD3, CD4, CD8, CD28+, naïve, and subpopulations of memory T cells by using flow cytometry. Furthermore, using the Flow-FISH methodology, the CD4+CD45RO+, CD4+CD45ROneg, CD8+CD28+, and CD8+CD28negT cell telomere lengths were measured. RESULTS: There was a greater proportion of effector memory T CD4+ cells and longer telomeres in CD8+CD28+ T cells in the moderate physical fitness group than in the other groups. There was a higher proportion of terminally differentiated memory effector T cells in the low physical fitness group. CONCLUSION: A moderate physical activity may positively influence the telomere shortening of CD28+CD8+T cells. However, additional studies are necessary to evaluate the importance of this finding with regard to immune function responses in older men.